2021
DOI: 10.3390/su13084301
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Concern, Attitude and Intention in Understanding Student’s Anti-Littering Behavior Using Structural Equation Modeling

Abstract: Concerns about the environment began to rise as various issues such as littering increased. Littering is one of the problems involving the environment, and higher education campuses are also actively practising anti-littering to show their efforts. The aim of this study is to test the relationship between environmental concern, attitude and intention on anti-littering using Theory of Planned Behavior Extended Model. A total of 303 students of the Polytechnic Malaysia campus were respondents in this study and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 32 publications
4
22
0
1
Order By: Relevance
“…College students who use metaverse technology to learn basketball have a positive causal relationship with behavioral intentions. It confirms previous findings ( Ibrahim et al., 2021 ; Q. Jiang, J. Sun, C. Yang, & C. J. S. Gu, 2022 ; Lee et al., 2021 , Lee et al., 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…College students who use metaverse technology to learn basketball have a positive causal relationship with behavioral intentions. It confirms previous findings ( Ibrahim et al., 2021 ; Q. Jiang, J. Sun, C. Yang, & C. J. S. Gu, 2022 ; Lee et al., 2021 , Lee et al., 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the data was analysed using the SPSS Amos 24.0 Statistical Software Package to test the Structural Equation Modelling (SEM) [113]. SEM is widely used in social science research [114] because it provides a flexible framework for constructing and analysing complicated interactions across different variables, allowing researchers to verify the validity of a theory using empirical models [115]. Its capacity to manage measurement error, one of the most significant constraints of most studies, is perhaps its greatest advantage [116].…”
Section: Measurement Modellingmentioning
confidence: 99%
“…Previous studies indicated that attitude mediates the relationship between emotion and intention (Gilchrist et al, 2019;Ibrahim et al, 2021b;Taylor et al, 2016). According to Bamberg (2003), environmental concern indirectly affects intention through attitude as a mediator and is also supported by several studies (Chen, & Tung, 2014;De Groot & Steg, 2007;Ibrahim et al, 2021a;Kumar et al, 2022;Onurlubaş, 2018;Zhu et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 76%